MBA research and the strategic challenges of practising managers in South Africa - MANYEMA, SHAW (My University, 2012)
Managers of South African listed companies are faced with a variety of strategic challenges that they require to find solutions for to ensure the continued existence of their operations. Fortunately, South Africa has several business schools that are capable of conducting research which should provide solutions to some of these strategic challenges. In addition, South Africa has legislated research as an integral part of masters’ degrees and this should ensure a continuous flow of new ideas that should benefit local companies. However, despite the existence of several business schools in South Africa, practising managers seem not to be getting research output from MBA graduates that is relevant to the challenges they are facing. In particular, managers contend that MBA research output has been influenced by the scientific research approach, which elevates academic rigour at the expense of practical relevance. The purpose of this research was to identify the strategic challenges faced by managers of South African listed companies in 2008 and determine the extent to which MBA research subject areas in 2008 matched the strategic challenges faced by these companies. Using a qualitative approach, content analysis was performed on 140 annual reports of JSE listed companies for 2008, and on the 2008 research reports produced by Wits Business School, University of Stellenbosch Business School, University of Cape Town’s Graduate School of Business and University of Pretoria’s Gordon Institute of Business Science. The challenges identified from the annual reports were compared to the research subject areas from the MBA students’ reports from the 4 business schools. The findings of this study were that there were mismatches in 2008 between the challenges that managers faced and the MBA research subject areas. More work need to be done to align the research output of MBA students with the needs of managers. Increased collaboration between faculty, students and managers is required to ensure that students engage in relevant and practical research for the benefit of all stakeholders.
MBA thesis - WBS
Keywords: Strategy; Research output; Operation management